Clinicoepidemiological characteristics of viral hepatitis in migrants and travellers of the +Redivi network. Issue 29 (May 2019) - ,; Aguilera, Paloma; Serrano, María Martínez; Rodriguez, Magdalena García; Menendez, Marta Díaz; Meije, Yolanda; Martínez-Montauti, Joaquim; Sanz, Xavier; Tenza, Isabel Pacheco; Cuello, Inmaculada Gonzalez; López, Belén Martínez; LLenas, Jara; et al.
Abstract: Background: Continuous growth of mobile populations has influenced the global epidemiology of infectious diseases, including chronic and acute viral hepatitis. Method: A prospective observational multicentre study was performed in a Spanish network of imported infections. Viral hepatitis cases from January 2009 to September 2017 were included. Results: Of 14, 546 records, 723 (4.97%) had imported viral hepatitis, including 48 (6.64%) acute cases and 675 (93.36%) chronic cases. Of the 48 acute cases, 31 were travellers and immigrants returning from visiting friends or relatives (VFR), while 19 (61%) were acute Hepatitis A or Hepatitis B. Only 18.2% of VFR immigrants and 35% of travellers received pre-travel advice. Acute hepatitis was more frequent in VFR immigrants (AOR 2.59, CI95% 1.20–5.60) and travellers (AOR 2.83, CI95% 1.46–5.50) than immigrants. Of the 675 Chronic cases, 570 were immigrants, and 439 (77%) had chronic Hepatitis B. Chronic hepatitis was more frequent in immigrants (AOR 20.22, CI95% 11.64–35.13) and VFR immigrants (AOR 11.12, CI95% 6.20–19.94) than travellers. Conclusions: Chronic viral hepatitis was typical of immigrants, acute viral hepatitis was common among travellers, and VFR immigrants had mixed risk. Improving pre-travel consultation and screening of immigrants may contribute to preventing new cases of viral hepatitis and avoiding community transmission.